Strategi Pengembangan Jamu Jawa Tradisional CV. Santoso di Kabupaten Banyuwangi, Jawa Timur - Dini Nafisatul Mutmainah; Ahmad Haris Hasanuddin Slamet; Dian Kumaila Dewi; Nadhirotul Diniyah (Food Scientia : Journal of Food Science and Technology, 2022)
CV. Santoso is a traditional Javanese herbal medicine company in Banyuwangi Regency. The development of the herbal medicine industry in Indonesia is growing very rapidly. This condition pushes CV. Santoso to determine the right marketing strategy so that their products can compete with various herbal products in the market. This study aimed to analyze the internal and external factors of CV. Santoso, to find out several alternative development strategies and the appropriate priority strategy for the company. The method in this study used a qualitative descriptive approach. The analysis techniques used were SWOT analysis and AHP analysis. The results showed that promotional activities by creating a promotion team were the main priority strategy for the development of traditional Javanese herbal medicine of CV. Santoso. The weight value generated from the top priority strategy was 0.139, using a logical consistency of 8%. He main priority strategy was to create a promotion team that can be implemented to expand product marketing through print media, mass media and social media.